Association of critical thinking disposition with personality traits and differentiation of self in medical undergraduates, a multicenter cross-sectional study in China - Zeng, Zixuan; Wang, Xiaohan; Sun, Hengxing; Thai, Jessica; Gan, Yafen; Li, Enxiu; Huang, Lei (Frontiers in Medicine, 2025)
BackgroundCritical thinking is one of the seven essential competencies of the Global Minimum Essential Requirements in Medical Education. It is essential to cultivate medical students’ critical thinking as it influences their clinical decision-making. The undergraduate years represent a critical period for medical students in terms of personality development and self-differentiation, which are essential foundations for shaping critical thinking. Therefore, this multicenter cross-sectional study aimed to explore the relationships of critical thinking disposition with personality traits and differentiation of self in medical undergraduates.MethodsA total of 1,338 medical students from three institutions in China were selected for this study using a stratified cluster sampling method. The Critical Thinking Disposition Inventory-Chinese Version (CTDI-CV), Eysenck Personality Questionnaire (EPQ) and Differentiation of Self Inventory-Revised (DSI-R) were applied to assess medical students’ critical thinking disposition, personality traits and differentiation of self. Multiple linear regression analysis was conducted to test the relationships of critical thinking disposition with personality traits and differentiation of self. Binary logistic regression model was established for sensitivity analysis.ResultsLinear regression analysis showed that psychoticism and neuroticism could negatively influence critical thinking disposition [β, 95% confidence interval (CI) = −0.363 (−0.411, −0.316); −0.129 (−0.189, −0.070)]. Conversely, extraversion and differentiation of self could positively influence critical thinking disposition [β, 95% CI = 0.145 (0.096, 0.194); 0.279 (0.224, 0.334)]. The results of the binary logistic regression were consistent with those of the linear regression model.DiscussionThis study suggested the potential need for tailored critical thinking development strategies for medical students with different personality traits and degrees of differentiation of self.